Pengaruh Terpaan Berita Pilgub Bali di Instagram @tribunbali terhadap Partisipasi Politik Pemilih Pemula di Kabupaten Tabanan dalam Pilkada 2018 - Wiguna, I Putu Kumara; Amanda Gelgel, Ni Made Ras; Pradipta, Ade Devia (E-Jurnal Medium, 2019)
ABSTRACTd In 2018, the election of governor and deputy governor ofcBali for the period of 2018-2023 was conducted. Tabanan Regency has the highest electoral participation rate of 81.34%. This research aims to see how Instagram @tribunbali influence the political participation of the novice voters in Tabanan Regency. This research uses quantitative explanatory methods with uses and effects theory. The data analysis technique is a simple linearwregression analysis with SPSS 18 program. The results of this research showed the news of the election of governor and deputywgovernorwof Bali 2018 on Instagram @tribunbali have a positive influence on the political participation of novice voters in Tabanan Regency. When the news of the governor and deputy governor of Bali election on Instagram @tribunbali increased, political participation of novice voters in Tabanan Regency is getting higher. Keywords: Instagram,Wpolitical participation,Wnovice voters, newsIexposure, usesPand effects theory